Allogeneic CD27‐depleted cells in adoptive cell therapy. Issue 2 (28th January 2019) - Talleur, Aimee C.; Métais, Jean‐Yves; Li, Ying; Throm, Robert E.; Tillman, Heather; Rooney, Barbara; Moustaki, Ardiana; Leung, Wing
Abstract: Adoptive cell therapy (ACT) has emerged as an effective treatment for some cancers. However, allogeneic cell applications are in part limited by the risk of alloreactive T‐cell subsets causing graft‐versus‐host‐disease (GVHD). We therefore hypothesized that the use of CD27‐depleted cells (containing natural killer [NK] cells and effector memory T‐cells; without naïve or central memory T‐cells) would offer protection from pathogens and GVHD, while also providing anticancer activity when genetically engineered with a chimeric antigen receptor (CAR). In this work, cell phenotypes were evaluated using flow cytometry. In vitro immunologic memory and alloreactivity were tested using lymphocyte proliferation assays. In vivo GVHD potential was assessed using NOD scid gamma (NSG) mice. Anticancer activity of CAR‐transduced CD27‐depleted cells was tested in vitro via a cytotoxicity assay and in vivo using NSG mice. Our results confirmed that the CD27‐depleted cell fraction was enriched for NK cells, effector memory CD4 pos T cells and terminal effector memory CD8 pos T cells. CD27‐depleted cells had strong immunologic response against common pathogens in vitro, and less GVHD potential in vitro and in vivo. CD27‐depleted cells could be transduced with a CAR vector produced by stable cell lines, and demonstrated significant antileukemic activity in vitro and in vivo. These findings suggest that CD27‐depletion is a promising approach to using allogeneic cells in ACT, potentially providing infection and cancer control simultaneously but having low risk of causing GVHD.